-1=-4+b/6

Simple and best practice solution for -1=-4+b/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1=-4+b/6 equation:



-1=-4+b/6
We move all terms to the left:
-1-(-4+b/6)=0
We add all the numbers together, and all the variables
-(b/6-4)-1=0
We get rid of parentheses
-b/6+4-1=0
We multiply all the terms by the denominator
-b+4*6-1*6=0
We add all the numbers together, and all the variables
-1b+18=0
We move all terms containing b to the left, all other terms to the right
-b=-18
b=-18/-1
b=+18

See similar equations:

| 9-q+2=-4 | | 4x+17+2x-23=90 | | 12=10+v/5 | | 9+4=4q-8 | | x(x+2)-10(x+2)=0 | | -(5x+7)=4x+2 | | -86=-8-6b | | y(y+6)=72 | | 35=a/3+4 | | 8+7x-4x=13+2x | | 1/3(x+1)=1/2(x-2) | | 19+7y=5 | | 4+c15=-9 | | 8+(x-6)=-2=+2x-2 | | 7+2x=1-2x | | 2x=2235-5x | | 90+.6x=60+.90x | | 3x+76=144 | | 8-v=19 | | |x|=1.4 | | (12-3x)^3=0 | | A/10-3a/20=5/4-3a/10 | | 3(x+14)=27 | | 60/64=x/48 | | 1.6×n=6.4 | | 3x-7=11x-15 | | -2v+7=1+3v-6v | | X/12=1/3-x/12 | | 90=-18v | | -8v+6(v+7)=38 | | 9(x-1)-8=5x+4(-3+x) | | 9(x-1)-8=5x+4(-3+x |

Equations solver categories